PENGARUH MODEL PEMBELAJARAN BLENDED LEARNING DI ERA NEW NORMAL TERHADAP HASIL BELAJAR SISWA DI MI KHADIJAH MALANG - Siti Romlah; Ika Ratih Sulistiani; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
The problem in the study found symptoms or difficulties in student learning outcomes that affected because the online learning process caused internal factors, namely conditions that emerged from within the student, physical aspects, motivation, willingness to learn, and self-confidence. as well as external factors in the family and community environment. The purpose of this study was to determine: how the effect of blended learning on student learning outcomes at MI Khadijah Malang. The subjects of this study were all students in grade 2, totaling 56 students. Data collection techniques using the test technique. Furthermore, the data collected were analyzed using the T-test formula. Based on the results of the study, it can be concluded that there is an effect of blended learning on student learning outcomes in class 2 MI Khadijah Malang because the sig value is smaller than 0.05 or stated at 0.000 <0.05, meaning that the hypothesis is accepted and has a significant effect. So it can be concluded that Hₒ is rejected and Hₐ is accepted. Kata kunci: blended learning, learning outcomes